A comparison study of three physical activity measurement tools examining acceptability in people with psychosis. (April 2020) - Suetani, Shuichi; Chapman, Justin; Korman, Nicole; Chapman, Carly; Dodd, Cassandra; Dark, Frances; Parker, Stephen; Siskind, Dan
Objective: To compare the acceptability of three distinct physical activity measurement tools in people with psychosis: an objective measurement tool, a self-report measure, and an exercise capacity test. Methods: We measured the completion rate for each measurement tool. Participants rated the ease/difficulty of each measure using a 7-point Likert scale. Participants were also asked to rank the three tools in order of the ease of use. Results: Sixty-six per cent (46/69) of participants completed all three assessment tools, and 60.9% (42/69) completed the acceptability questionnaire. The majority of the participants found it easy to complete all three measurement tools. The majority (52.8%) of the participants ranked the objective measurement tool as the easiest to use. Conclusion: All three measures were acceptable to people with psychosis, but objective measurement tools may be easier to use.